Computational Architecture of Digital Marketing of Toyota Corporation - Dedi Iskamto; Adryan Edhie Wicaksono (Postgraduate, University of Mataram, 2023)
Toyota uses social media marketing strategies Instagram to promote its products and include important information about the automotive industry to influence social media marketing, e-wom, brand image, brand trust, and purchase intention. The research aims to determine the influence of Toyota's social media marketing, brand image, brand trust, and purchase intention. The sample taken in this research was 385 respondents using quantitative methods and data analysis techniques using SmartPLS. Based on the results of the analysis it was found that Social Media Marketing has a significant and positive effect on Purchase Intention, Social Media Marketing has a significant and positive effect on Brand Trust, Social Media Marketing has a significant and positive effect on the Brand Image, Brand Trust has a significant and positive effect on Purchase Intention, Brand Image has a significant and positive effect on Purchase Intention, E-Wom moderate Social Media Marketing has a significant and positive effect on Purchase Intention at Toyota